Psychometric Properties of A Draw A Man Test To measure intelligence A Descriptive Study on A Sample of Tartous and Lattakia Children - Boubou, Mounzer; Mohamad, Hala; Shahin, Suhair (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research aims to identify the psychometrics characteristics of the "draw a man test", and placing special standards for its usage in the Syrian environment as well as discovering the differences between the tested sample individuals. According to their sex and age category. To achieve this, the descriptive approach has been followed . where this "draw a man test was applied upon a sample of 1026 child at kindergartens in the cities of tartous and lattakia . the COGAT test was used in order to verify the Criterion – Related validity, and hereafter are the most important results: The "draw a man test " can be used as a valid scale for measuring the intelligence levels in Syria, The test enjoys high levels of reliability which reached 0.96 using the reliability half method and 0,954 using Re-test reliability, The test enjoy high levels of validity ,Special standards were placed for the usage of the "draw a man test" at the kindergartens stage in Syria, There are difference found in the performances between the males and females In favor of females, There are difference found while taking "draw a man test" according to the variable of the different age stages Where the degree increases with the age.